2011
DOI: 10.5194/bg-8-3127-2011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon flux to woody tissues in a beech/spruce forest during summer and in response to chronic O<sub>3</sub> exposure

Abstract: Abstract. The present study compares the dynamics in carbon (C) allocation of adult deciduous beech (Fagus sylvatica) and evergreen spruce (Picea abies) during summer and in response to seven-year-long exposure with twice-ambient ozone (O 3 ) concentrations (2 × O 3 ). Focus was on the respiratory turn-over and translocation of recent photosynthates at various positions along the stems, coarse roots and soils. The hypotheses tested were that (1) 2 × O 3 decreases the allocation of recent photosynthates to CO 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…At the whole tree level, elevated O 3 affects allocation processes of photoassimilates. In mature trees, longterm exposure to twice ambient O 3 concentrations significantly reduced allocation to stems (Ritter et al 2011), which is well in line with the often-found reduction of stem growth in natural environments with high O 3 exposure (Karnosky et al 2005). Below ground, O 3 impaired source-sink relations are believed to reduce belowground C allocation (reviewed by Andersen 2003, typically resulting in lower root/shoot biomass ratios.…”
Section: Damages Caused By Ozonesupporting
confidence: 76%
“…At the whole tree level, elevated O 3 affects allocation processes of photoassimilates. In mature trees, longterm exposure to twice ambient O 3 concentrations significantly reduced allocation to stems (Ritter et al 2011), which is well in line with the often-found reduction of stem growth in natural environments with high O 3 exposure (Karnosky et al 2005). Below ground, O 3 impaired source-sink relations are believed to reduce belowground C allocation (reviewed by Andersen 2003, typically resulting in lower root/shoot biomass ratios.…”
Section: Damages Caused By Ozonesupporting
confidence: 76%
“…This suggests that F. crenata seedlings grown under the +CO 2 +O 3 allocated larger amounts of biomass to aboveground tissues than belowground tissues, resulting in higher S:R ratio and L:R ratio, and in lower RWR compared with other treatments (Table 3). Reduced C allocation into root has also been demonstrated in young [16,30,65] and mature trees of Fagus species under conditions of elevated O 3 [19]. However, in mature Fagus species, different responses to elevated O 3 were also observed, such as stimulation of root growth [66,67] and no changes in carbon allocation into belowground tissues [68].…”
Section: Discussionmentioning
confidence: 89%
“…Elevated CO 2 stimulates plant growth by enhancing photosynthetic carbon assimilation [10][11][12], although long-term exposure to elevated CO 2 results in photosynthetic down-regulation, especially under limiting nutrient conditions [13,14]. Elevated O 3 concentrations reduce net CO 2 assimilation (A) and accelerate leaf senescence [15,16], potentially resulting in substantial losses of the C-sink strengths in trees [9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress, e.g. induced by chronic ozone exposure, can reduce the allocation of recent photosynthates to stem and root respiration (Ritter et al, 2011;cf. also Brüggemann et al, 2011).…”
mentioning
confidence: 99%